Air pollution and airway resistance at age 8 years - the PIAMA birth cohort study - Finke, Isabelle; de Jongste, Johan C; Smit, Henriette A; Wijga, Alet H; Koppelman, Gerard H; Vonk, Judith; Brunekreef, Bert; Gehring, Ulrike (BioMed Central, 2018)
BACKGROUND: Air pollution has been found to adversely affect children's lung function. Forced expiratory volume in 1 s and forced vital capacity from spirometry have been studied most frequently, but measurements of airway resistance may provide additional information. We assessed associations of long-term air pollution exposure with airway resistance. METHODS: We measured airway resistance at age 8 with the interrupter resistance technique (Rint) in participants of the Dutch PIAMA birth cohort study. We linked Rint with estimated annual average air pollution concentrations [nitrogen oxides (NO2, NOx), PM2.5 absorbance ("soot"), and particulate matter < 2.5 μm (PM2.5), < 10 μm (PM10) and 2.5-10 μm (PMcoarse)] at the birth address and current home address (n = 983). Associations between air pollution exposure and interrupter resistance (Rint) were assessed using multiple linear regression adjusting for potential confounders. RESULTS: We found that higher levels of NO2 at the current address were associated with higher Rint [adj. mean difference (95% confidence interval) per interquartile range increase in NO2: 0.018 (0.001, 0.035) kPa·s·L- 1]. Similar trends were observed for the other pollutants, except, PM10. No association was found between Rint and exposure at the birth address. CONCLUSIONS: Our results support the hypothesis that air pollution exposure is associated with a lower lung function in schoolchildren.
Keywords: Air pollution; Children; Interrupter resistance; Particulate matter; Nitrogen dioxide